2007
DOI: 10.1002/jsfa.2856
|View full text |Cite
|
Sign up to set email alerts
|

In vitro gas production profile and the formation of end products from non‐ washable, insoluble washable and soluble washable fractions in some concentrate ingredients

Abstract: A procedure that mimics washing in the in situ incubation technique, combined with an in vitro gas and volatile fatty acids (VFAs) production technique, was used to verify the assumption that rumen degradation behaviour of material washed out of nylon bags is instantaneous and complete. In a 6 × 4 factorial arrangement of treatments with three replicates, fractions of maize, barley, milo, yellow peas, lupins (a mixture of white and spotted lupins) and round-seeded brown faba beans were subjected to an in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…46 This observation is in line with our findings in the current study. Indeed, the multiphasic manner of gas production observed with the fermentation of the SWF of peas and faba beans in a previous study 13 was not observed in the current study (data not shown).…”
Section: Effect Of Processing On In Vitro Cumulative Gas Production Kcontrasting
confidence: 81%
See 2 more Smart Citations
“…46 This observation is in line with our findings in the current study. Indeed, the multiphasic manner of gas production observed with the fermentation of the SWF of peas and faba beans in a previous study 13 was not observed in the current study (data not shown).…”
Section: Effect Of Processing On In Vitro Cumulative Gas Production Kcontrasting
confidence: 81%
“…The same tendency of increasing unknown residual fraction of the SWF was observed in E-and EP-treated barley. 13 It has been reported that soluble fibres increase after pelleting 40 and extrusion. 41 However, the authors believe that further experiments has to be carried out to bear out this theory.…”
Section: Effect Of Processing On In Vitro Cumulative Gas Production Kmentioning
confidence: 99%
See 1 more Smart Citation
“…For incubation times of 72 h, 36 h, 12 h, 6 h and 2 h, seven, six, five, four and two bags of each sample were randomly incubated in the rumen of each cow, respectively. Immediately after retrieval, all bags were placed in cold tap water to stop microbial fermentation and then washed manually five times in cold tap water followed by oven drying at 55 °C for 48 h. The 0 h incubation samples were washed by the procedure described by Azarfar et al [25] to fractionated washable fraction (W) into a truly washable soluble fraction (S) and a washable but insoluble fraction (WI). Since the WI was almost zero, for the purpose of modelling it was assumed that the W fraction equalled the S fraction.…”
Section: Methodsmentioning
confidence: 99%
“…For the incubation times of 72, 36, 12, 6 and 2 h, seven, six, five, four and two bags of each sample were incubated in the rumen of each cow, respectively. Immediately after retrieval, all bags were placed in cold tap water to stop the microbial fermentation and then washed manually five times in cold tap water followed by oven drying at 558C for 48 h. The 0 h incubation samples were washed by the procedure described by Azarfar et al (2007) to fractionate the washout fraction (W) into a water soluble fraction (S) and an insoluble fraction (WI). As the WI was almost zero, for the purpose of modeling it was assumed that the W fraction was equal to the S fraction.…”
Section: Animals and Dietsmentioning
confidence: 99%